2009
DOI: 10.1183/09031936.00043309
|View full text |Cite
|
Sign up to set email alerts
|

Is INTERdisciplinary COMmunity-based COPD management (INTERCOM) cost-effective?

Abstract: The study aimed to estimate the cost-effectiveness of interdisciplinary communitybased chronic obstructive pulmonary disease (COPD) management in patients with COPD.We conducted a cost-effectiveness analysis alongside a 2-yr randomised controlled trial, in which 199 patients with less advanced airflow obstruction and impaired exercise capacity were assigned to the INTERCOM programme or usual care. The INTERCOM programme consisted of exercise training, education, nutritional therapy and smoking cessation counse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
4
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 40 publications
1
72
4
4
Order By: Relevance
“…En el 45,5% (n=10) de los estudios fueron mayoría los hombres, frente a un 40,9% (n=9) donde la mayor prevalencia eran mujeres y en un 13,6% (n=3) fue equitativo el reparto entre sexos, todos los estudios llevados a cabo en España muestra unas diferencias muy significativas de la prevalencia de la EPOC en el sexo masculino. La media de edad de todos los estudios es de 66,4 años, siendo la comorbilidad más frecuente las enfermedades coronarias, de los estudios que así lo analizaron (n=5) (45,46,60,67,73) . En uno de los estudios que así lo recogen afirman que el 90% de los pacientes se vacunó contra la gripe el año anterior, no teniendo los resultados de incidencia de la vacunación tras la implementación del programa de educación terapéutica (47) .…”
Section: Participantes/ Reclutamientounclassified
See 2 more Smart Citations
“…En el 45,5% (n=10) de los estudios fueron mayoría los hombres, frente a un 40,9% (n=9) donde la mayor prevalencia eran mujeres y en un 13,6% (n=3) fue equitativo el reparto entre sexos, todos los estudios llevados a cabo en España muestra unas diferencias muy significativas de la prevalencia de la EPOC en el sexo masculino. La media de edad de todos los estudios es de 66,4 años, siendo la comorbilidad más frecuente las enfermedades coronarias, de los estudios que así lo analizaron (n=5) (45,46,60,67,73) . En uno de los estudios que así lo recogen afirman que el 90% de los pacientes se vacunó contra la gripe el año anterior, no teniendo los resultados de incidencia de la vacunación tras la implementación del programa de educación terapéutica (47) .…”
Section: Participantes/ Reclutamientounclassified
“…En todos los estudios, salvo uno (64) , el modo de educación fue grupal, en algunos de los casos además se realizó de un plan individual (n=9) (45,46,48,55,60,64,71,73,74) , uso de folletos informativos para reforzar la educación (n=8) (5,45,48,53,54,60,67,71) , seguimiento telefónico (n=3) (45,70,71) o utilización de diario (n=3) (50,53,71) . El contenido de las sesiones educativas fue: en 18 artículos (81,8%) en sus sesiones educativas hablan sobre el conocimientos sobre la EPOC, con los siguientes componentes: anatomía y fisiología (n=3) (50,54,63) , descripción de la enfermedad (n=10) (5,(45)(46)(47)49,55,60,64,67,70) , signos y síntomas de la EPOC (n=3) (54,57,74) , signos y síntomas de las exacerbaciones (n=10) (50,54,55,57,60,63,64,…”
Section: Intervencionesunclassified
See 1 more Smart Citation
“…For Ferber, it describes the constraints (in terms of obligations, abilities, and skills) and the consequences (in terms of capacity, authorizations) that the agent will receive in this role [14]. Hoogendoorn considers that assigning a role to an agent can be dynamic [15].…”
Section: Role Changing In the Proposed Mas Mass Offer Two Perspectmentioning
confidence: 99%
“…[2][3][4] Clinical trials have shown that inhaled bronchodilators and to a lesser extent corticosteroids improve symptoms and reduce exacerbations. 2,5,6 Notably, recent studies suggest that lung function decline is fastest in early instead of advanced COPD, and that maintenance treatment with inhaled medication is also beneficial in moderate, and not only in severe, obstruction.…”
mentioning
confidence: 99%